Credit Borrower Sector of Economy and Credit Risk For Banks - Joanna Stępińska (Finanse i Prawo Finansowe)
The purpose of the article. Business entities in different industries operate differently. Therefore, different sectors are characterized, among other things, by different profitability, the need for external financing, and, consequently, a different level of risk of default on credit commitments to banks. Borrowers from specific industries may be, from the perspective of banks' interests, better or worse customers and contribute to strengthening or weakening the quality of their credit portfolios.